Spinal anaesthesia with bupivacaine and intrathecal morphine versus combined spinal-epidural anaesthesia using bupivacaine and epidural infusion of bupivacaine plus fentanyl for postoperative analgesia after hip and knee arthroplasty. - Mohd Azizan G; Karis M; Noordin Y (Department of Surgery, UKM Medical Centre, 2013)
This randomised single-blinded study was conducted to evaluate if there was any difference between spinal anaesthesia with hyperbaric bupivacaine 0.5% and intrathecal morphine 0.2mg and combined-spinal epidural using hyperbaric bupivacaine 0.5% with epidural infusion of bupivacaine 0.1% plus fentanyl 2.0μg/ml for 24 hours, postoperative analgesia following hip and knee arthroplasty, in terms of pain score and side effects (nausea, vomiting, pruritus and respiratory depression). Eighty patients ASA I or ASA II, aged between 18 to 75 years who underwent knee and hip arthroplasty of approximately 3-4 hours, duration were recruited. They were randomly allocated to one of two groups by using computer generated randomised numbers. The pain score during the postoperative period was evaluated using Visual Analogue Score (VAS pain score) and the side effects were documented and treated accordingly. Results showed that patients in Group 1 and Group 2 were comparable in terms of age, gender, height, weight and race. There was no statistical difference in VAS pain score between the two groups at all times intervals. However, patients in Group 1 had a higher incidence of nausea and pruritus than patients in Group 2. None of the patients in either group, experienced respiratory depression. Thus, it was concluded that both intrathecal morphine 0.2mg and epidural infusion of bupivacaine 0.1% plus fentanyl 2.0μg/ml were comparable in providing postoperative analgesia up to 24 hours following hip and knee arthroplasty. Nevertheless, the use of spinal morphine led to a higher incidence of side effects namely nausea and pruritus.